In situ sequencing identifies TMPRSS2–ERG fusion transcripts, somatic point mutations and gene expression levels in prostate cancers. Issue 2 (4th August 2014) - Kiflemariam, Sara; Mignardi, Marco; Ali, Muhammad Akhtar; Bergh, Anders; Nilsson, Mats; Sjöblom, Tobias
Abstract Translocations contribute to the genesis and progression of epithelial tumours and in particular to prostate cancer development. To better understand the contribution of fusion transcripts and visualize the clonal composition of multifocal tumours, we have developed a technology for multiplex in situ detection and identification of expressed fusion transcripts. When compared to immunohistochemistry, TMPRSS2–ERG fusion‐negative and fusion‐positive prostate tumours were correctly classified. The most prevalent TMPRSS2–ERG fusion variants were visualized, identified, and quantitated in human prostate cancer tissues, and the ratio of the variant fusion transcripts could for the first time be directly determined by in situ sequencing. Further, we demonstrate concurrent in situ detection of gene expression, point mutations, and gene fusions of the prostate cancer relevant targets AMACR, AR, TP53, and TMPRSS2–ERG. This unified approach to in situ analyses of somatic mutations can empower studies of intra‐tumoural heterogeneity and future tissue‐based diagnostics of mutations and translocations. Copyright © 2014 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd